2015
DOI: 10.1159/000433524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Donepezil on Extrapyramidal Symptoms in Patients with Dementia with Lewy Bodies: A Secondary Pooled Analysis of Two Randomized-Controlled and Two Open-Label Long-Term Extension Studies

Abstract: Background/Aims: The aim of this study was to clarify the effects of donepezil on extrapyramidal symptoms in patients with dementia with Lewy bodies (DLB). Methods: Using pooled datasets from phase 2 and 3, 12-week randomized, placebo-controlled trials (RCT, n = 281) and 52-week open-label long-term extension trials (OLE, n = 241) of donepezil in DLB, the effects of donepezil on the incidence of extrapyramidal adverse events (AEs) and on the Unified Parkinson's Disease Rating Scale (UPDRS) part III were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
(58 reference statements)
1
6
0
1
Order By: Relevance
“…Although ChEI treatment can theoretically worsen extrapyramidal symptoms, the UPDRS part III scores were not significantly associated with the plasma donepezil concentration in the present analysis. This suggests that increasing the donepezil dose to 10 mg/day would not necessarily exacerbate parkinsonism, as shown previously [9,11,29]. Although no correlation between plasma concentration and worsening of parkinsonism was not demonstrated, it is still important to observe parkinsonism during donepezil treatment in these patients.…”
Section: Discussionsupporting
confidence: 62%
“…Although ChEI treatment can theoretically worsen extrapyramidal symptoms, the UPDRS part III scores were not significantly associated with the plasma donepezil concentration in the present analysis. This suggests that increasing the donepezil dose to 10 mg/day would not necessarily exacerbate parkinsonism, as shown previously [9,11,29]. Although no correlation between plasma concentration and worsening of parkinsonism was not demonstrated, it is still important to observe parkinsonism during donepezil treatment in these patients.…”
Section: Discussionsupporting
confidence: 62%
“…The protocols were approved by the institutional review board at each participating centre. The results of the studies have previously been reported [12,13,14,15,16]. …”
Section: Methodsmentioning
confidence: 88%
“…We have previously conducted 3 clinical trials [12,13,14,15,16] on donepezil for DLB including 2 RCTs [12,14] that enrolled a total of 281 patients diagnosed with probable DLB according to the original consensus criteria [2]. These studies were conducted 3 years apart.…”
Section: Introductionmentioning
confidence: 99%
“…Although donepezil was shown as beneficial with respect to cognition in mild to moderate dementia [ 80 , 81 , 82 , 83 ], and also moderate dementia with Parkinson’s disease, donepezil therapy did not change motor PD symptoms [ 84 , 85 ]. Furthermore, donepezil treated dementia with Lewy body, without relevant worsening of extrapyramidal symptoms [ 86 ]. However, others stated that donepezil treatment could cause adverse motor effects in a subset of patients with parkinsonian dementia [ 87 , 88 , 89 , 90 ]; worsened activities of daily living mobility in patients with progressive supranuclear palsy [ 91 ]; and deteriorated motor behavior in patients with dystonic reactions [ 92 ].…”
Section: Discussionmentioning
confidence: 99%